Insight into the mechanism revealing the peroxidase mimetic catalytic activity of quaternary CuZnFeS nanocrystals: colorimetric biosensing of hydrogen peroxide and glucose1. Issue 19 (21st May 2015) - Dalui, Amit; Pradhan, Bapi; Thupakula, Umamahesh; Khan, Ali Hossain; Kumar, Gundam Sandeep; Ghosh, Tanmay; Satpati, Biswarup; Acharya, Somobrata
<x xml:space="preserve">Abstract</x> CuZnFeS nanocrystals show robust peroxidase-like catalytic activity for H2O2 and glucose detection.